Pendidikan Kesehatan Komunitas P2WKSS untuk Mengendalikan Stunting di Kecamatan Lakbok - Yuyun Rahayu; Ima Sukmawati; Heni Heryani; Nisa Rahmawati; Nabil Ridla Firdaus (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Stunting is a condition in which a child has an unbalanced height ratio for his age, due to lack of nutrition so that the child's growth is stunted. One of the causes of stunting in toddlers is the lack of parental knowledge about stunting. This community service activity is carried out by empowering the community regarding stunting. It is hoped that after this program, the community and parents will know about stunting control and pay more attention to the growth of babies and toddlers. Objective: This community service activity is carried out by empowering the community regarding stunting which is expected after this program is carried out, the community and parent know about stunting control and pay more attention to the growth of infants and toodlers. Method: This activity was carried out by providing counseling through 3 stages, namely interviews, providing education about stunting, evaluation.   Result: of the 48 respondents before the counseling who knew about stunting only 20 people (41.6%) after the counseling, the knowledge of parents increased to 40 people (83.3%). Parents are able to apply and understand how to provide good nutrition and pay attention to hygiene in infants and toddlers. Conclusion: this service activity has succeeded in increasing parents' knowledge about stunting so that they play a major role as the main guide for the growth and development of babies and toddlers by paying more attention to nutritional needs and child development.